A Study of the Relationship Between the Liquid Limit and the Shear Angle of Fully Softened Clay with Residual Clay in Problematic Clay Formation in Tulungagung Regency - Kukuh Mahi Sudrajat; Sri Prabandiyani Retno Wardani; Kresno Wikan Sadono (Green Publisher Indonesia, 2026)
The distribution of problematic clay rocks, or called clay shale or stiff oc (overconsolidated clay), in Indonesia is not widely known or understood by the public or construction actors regarding the potential of the nature of these rocks. Problematic clay stone is a type of clay rock that has significant shrinkage properties, especially if exposed to water and cut loss of overburden pressure. These properties can cause geotechnical problems such as soil shifts and damage to the building structures that are on them. The target of the study was to identify the values of fully softened and residual shear strength, the researcher also examined the correlation of the liquid limit in these soil types. Testing is carried out by consolidation normally. The data taken by the researcher is problematic clay soils in Tulungagung Regency, which shows a pattern of shear stress curve to normal stress similar to that of Bearpaw Shale soil, which is nonlinear in fully softened conditions and more linear in residual conditions. The results of the study show that the characteristics of problematic clay are included in the category of high plasticity clay and have high sensitivity to changes in moisture content. The relatively high development potential results of the Free Swell Index (FSI) test showed 65% and based on the classification of development potential, this value was included in the medium to high category.